Search for Four-Charged Lepton from Decay Doubly-Charged Higgs Pair Production at the Hadron Colliders (Global Journal of Science Frontier Research, 2014)
The Left-Right symmetry Model (LRSM) is an extension of the Standard Model based on the gauge symmetry group SU(3)C × SU(2)L × SU(2)R × U(1)B-L predicts by existence new particles like doubly-charged Higgs boson, W' new charged boson, Z' new neutral boson and heavy neutrinos. In this work we present an analysis for production four-charged lepton in final state produced via decaying a pair of doubly-charged Higgs boson in the context of LRSM by using Monte Carlo simulation Techniques at both the Large Hadron Collider (proton-proton collisions) and the Fermilab Tevatron Collider (proton-antiproton collisions). In this analysis we assume that the branching ratio of decay channels of left-handed or right-handed doublycharged Higgs boson BR ( ±± → ℓ ± ℓ ± = 100%, ℓ = ± , ± , ± ). We carry out a Monte Carlo study of the (Left or Right) doubly charged Higgs pair production and decay to four-charged lepton via the process (̅ ) → ±± ±± → ℓ ± ℓ ± ℓ ± ℓ ± , ℓ = ± , ± , ± . From Monte Carlo simulation level the doubly-charged Higgs may be found at the LHC or at the Tevatron in the mass range up to 800 GeV.
Keywords: LHC; tevatron; left-right model; doubly charged higgs; monte carlo simulation